FAKTOR-FAKTOR YANG MEMPENGARUHI PRICE EARNING PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Jason Putra, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to analyze the effect of leverage, firm size, profitability, dividend payout, and liquidity on price earning in manufacturing companies listed on Indonesia Stock Exchange in 2015 – 2017. The sampling method used purposive sampling with total sample of 105 data which was taken on financial statement from www.idx.co.id. The collected data were analyzed by using Eviews 10. The research result that independent variables describe the dependent variable for55.0577% while 44.9423% is described by other factors. Independent variable ofleverage, firm size, profitability, and dividend payout do not have a significant effect on price earning, while liquidity has a significant effect on price earning.